2012
DOI: 10.1246/bcsj.20120198
|View full text |Cite
|
Sign up to set email alerts
|

Bioorganic Studies on the Key Natural Products from Venomous Mammals and Marine Invertebrates

Abstract: The discovery of new bioactive molecules, facilitated by a deeper understanding of nature, will advance our knowledge of biological processes and lead to new strategies to treat disease. Recent technological advancements including spectroscopic analyses and genetic approaches have provided outstanding opportunities for new discoveries, even in the case of scarce, unstable, and composite compounds. This account summarizes two recent aspects of bioorganic chemistry: mammalian venoms and antitumor marine macrolid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…It was found that the C34 N -methyl enamide moiety of ApA can be replaced with oximes without a significant loss of activity 35 36 . Also, several PEG-linked biotin conjugates of aplyronines have been shown to retain the potent activity of the natural products 37 38 . Based on these findings, amidopyrene 3 was converted to an alkoxyamine derivative possessing an aryltrifluoromethyldiazirine 39 40 group and a PEG linker, and coupled with ApA C34 aldehyde to afford an aplyronine A photoaffinity amidopyrene derivative (ApA–PaP, 4 ) ( Schemes S2 & S3, Supplementary Information ).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the C34 N -methyl enamide moiety of ApA can be replaced with oximes without a significant loss of activity 35 36 . Also, several PEG-linked biotin conjugates of aplyronines have been shown to retain the potent activity of the natural products 37 38 . Based on these findings, amidopyrene 3 was converted to an alkoxyamine derivative possessing an aryltrifluoromethyldiazirine 39 40 group and a PEG linker, and coupled with ApA C34 aldehyde to afford an aplyronine A photoaffinity amidopyrene derivative (ApA–PaP, 4 ) ( Schemes S2 & S3, Supplementary Information ).…”
Section: Resultsmentioning
confidence: 99%
“…Even several species of toxic birds, such as Pitohui kirhocephalus or Ifrita kowaldi , have been discovered [ 2 ]. However, despite the availability of new proteomic, genomic and chromatographic separation techniques, most venomous and poisonous animals remain unstudied [ 3 5 ]. Principally, toxins produced by insects, arachnids, snakes and frogs have been investigated thus far [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the availability of new proteomic, genomic and chromatographic separation techniques, most venomous and poisonous animals remain unstudied [ 3 5 ]. Principally, toxins produced by insects, arachnids, snakes and frogs have been investigated thus far [ 3 , 6 ]. Venoms produced by mammals remain mostly uncharacterized [ 3 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, it significantly reduced cellular viability and induced DNA fragmentation at 1 nM in HeLa S3 and human leukemia HL60 cells [79]. In addition, treatment with aplyronine A at 1 nM for 24 h led to potent caspase 3 activation in HeLa S3 cells, while treatment with aplyronine C did not, even at 100 nM [80]. These significant differences in apoptosis-related activities were consistent with their cytotoxicity, which highlighted the importance of the C7 trimethylserine moiety for the potent activities of aplyronine A.…”
Section: Dephosphorylation Of Fak and Caspase-dependent Apoptosis In mentioning
confidence: 96%